Mental rotation of feet in individuals with Body Integrity Identity Disorder, lower-limb amputees, and normally-limbed controls - Stone, Kayla; Bekrater-Bodmann, Robin (PLOS ONE, 2019)
Body Integrity Identity Disorder (BIID) is a non-psychotic condition wherein individuals desire amputation or paralysis of one or more healthy, fully-functioning limbs (predominantly the legs). Individuals with BIID have been suggested to have a mismatch between the perceived mental representation of the body and its actual physical structure, such that their desired identity matches that of a lower-limb amputee. Accordingly, studies have reported an altered central network involving body representation of the legs in BIID, but its relationship to behavior remains unclear. In the present study, we investigated the integrity of body representation in individuals with BIID, acquired lower-limb amputees, and normally-limbed controls using an online mental rotation task. Participants judged the laterality of left and right foot images presented from different views, orientations, and of different types. We expected BIID participants to be slower for mentally rotating images that corresponded to their affected legs than lower-limb amputees and normally-limbed participants. We found that the groups did not significantly differ in their performance. All participants were slower at judging feet presented in awkward postures than natural postures, replicating previous studies and validating our online paradigm. The results are discussed in terms of the robust nature of visual and sensorimotor lower-limb representations, whether related to the self or as prototype, in the context of disturbed lower-limb integrity.
Gesehen am 14.10.2019